2013
DOI: 10.1177/1524838013493520
|View full text |Cite
|
Sign up to set email alerts
|

Individual and Collective Dimensions of Resilience Within Political Violence

Abstract: Research has documented a link between political violence and the functioning of individuals and communities. Yet, despite the hardships that political violence creates, evidence suggests remarkable fortitude and resilience within both individuals and communities. Individual characteristics that appear to build resilience against political violence include demographic factors such as gender and age, and internal resources such as hope, optimism, determination and religious convictions. Research has also docume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 108 publications
3
45
0
1
Order By: Relevance
“…Similarly, community resilience is seen as the collective ability to adapt and recover from adversity as a population or a community [14-17]. However, similar to the discussion and debate around the concept of individual resilience, the concept of community resilience is also constantly evolving [18,19]. …”
Section: Introductionmentioning
confidence: 99%
“…Similarly, community resilience is seen as the collective ability to adapt and recover from adversity as a population or a community [14-17]. However, similar to the discussion and debate around the concept of individual resilience, the concept of community resilience is also constantly evolving [18,19]. …”
Section: Introductionmentioning
confidence: 99%
“…Relatedly, Sousa et al (2013) have reminded us that political violence targets more than the individual:…”
Section: Social Ecological Factorsmentioning
confidence: 99%
“…Following this approach, some researchers have examined community resilience, defined as 'positive collective functioning after a mass stressor ' Norris et al (2008, in Sousa et al 2013. Rather than a final outcome, community resilience is considered in the literature to be process-related (Nuwayhid et al 2011, cited in Sousa et al 2013.…”
Section: Social Ecological Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ben-Rafael et al claim that ethnicity, class and religion provide important foci for social cleavages, identifications, and consciousness in many societies, including Israeli society [33]. Earlier studies have indicated that the level of religiosity associated positively with resilience [28,34,35] and frequency of attending religious services is negatively associated with loneliness among a national representative sample of older U.S. veterans [36]. The current study examines level of religiosity as a potential predictor of individual SVR and we hypothesized that a higher level of religiosity would predict a higher level of resilience.…”
Section: Predictors Of Individual Resiliencementioning
confidence: 99%